2019
DOI: 10.21037/qims.2019.02.10
|View full text |Cite
|
Sign up to set email alerts
|

A scientometric analysis on hepatocellular carcinoma magnetic resonance imaging research from 2008 to 2017

Abstract: Background: With the development of new magnetic resonance imaging (MRI) techniques, an increasing number of articles have been published regarding hepatocellular carcinoma magnetic resonance imaging (HCCMRI) in the past decade. However, few studies have statistically analyzed these published articles. In this study, we aim to systematically evaluate the scientific outcomes of HCCMRI research and explore the research hotspots from 2008 to 2017. Methods: The included articles regarding HCCMRI research from 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Burst keywords detected by CiteSpace are considered important indicators of research frontiers or emerging topics over time (Yang, Wang, Wang, Yang, & Bian, 2019). As presented in Supplement S3, hip fracture, physical disability, functional status and prevention seemed to attract the most attention of peer researchers in the past 20 years, while social participation, social support, instrumental activity, frailty and loneliness have attracted research interest since 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Burst keywords detected by CiteSpace are considered important indicators of research frontiers or emerging topics over time (Yang, Wang, Wang, Yang, & Bian, 2019). As presented in Supplement S3, hip fracture, physical disability, functional status and prevention seemed to attract the most attention of peer researchers in the past 20 years, while social participation, social support, instrumental activity, frailty and loneliness have attracted research interest since 2015.…”
Section: Discussionmentioning
confidence: 99%
“…According to the keyword co-occurrence analysis, 55 keywords were detected. The keywords with strong citation bursts were explored through CiteSpace, and 24 keywords with the strongest strength in the last decades were identified (Table 4) [21,22]. Strength means citation burst, and it represents the increasing frequency of keywords in the corresponding period.…”
Section: Analysis Of Abstract and Burst Abstractmentioning
confidence: 99%
“…Although treatments have progressed in recent years, the prognosis of HCC patients remains poor because of the high recurrence rate . Studies have confirmed that the pathological grades of HCC have a strong relationship with microvascular invasion and play a vital role in predicting recurrence and long‐term prognosis . Thus, the development of an accurate preoperative assessment of the pathological grade of HCC could greatly benefit prognostic predictions for HCC patients.…”
mentioning
confidence: 99%